CAREER DEVELOPMENT AND WORK ENGAGEMENT: WORKPLACE SOCIAL CAPITAL AND ORGANIZATIONAL COMMITMENT AS MODERATOR AND MEDIATOR - Nurhayati, Mafizatun; Asih, Daru; Kasmo, Arief; Santosa, Awan (Jurnal Riset Bisnis dan Manajemen, 2024)
This study aimed to propose a social exchange theory in establishing the effects of career development support on work engagement, using organizational commitment and workplace social capital as mediation and moderation, respectively. It was conducted at the Bank Muamalat Indonesia in Jakarta, using Partial Least Square-Structural Equation Model. The results showed that career development support was able to increase work engagement and strengthen the relationship between employees and the company through organizational commitment. In this case, the higher tendency for employees to want, need, and feel obligated to stay in the company subsequently promoted vigour, dedication, and absorption, regarding increased work engagement characteristics. Organizational commitment was also able to partially mediate the relationship between career development and work engagement. Meanwhile, workplace social capital was unable to increase work engagement, although strengthened its relationship with career development support.